PENDIDIKAN KELUARGA DAN PERAN TEKNOLOGI DI ERA MILLENNIAL - Hikmatullah (Prosiding Temu Ilmiah Nasional Guru, 2023)
The progress of science and technology is increasingly unlimited and unstoppable. Therapid growth of technology culture, even this technology culture has entered remote areas, evenin many ways it is very dependent on technological engineering. The purpose of this study is todiscuss what is meant by the definition of family education, as well as technology used as alearning medium in the Millennial Era which is carried out through descriptive methods basedon literacy sources of books and journals related to technology which are used as a reference infamily education in the Millennial Era. Family education in the Millennial Era is an innovationor change in the results of rational human thinking in the Millennial Era, technology becomes acontrol in educational innovation. The role of technology in family education becomes a mediumand as a tool in delivering an education first and foremost. The millennial generation is oftenreferred to as the generation that is responsive to changes in modern times, the main study thattriggers a change is technology, during the period of human development in the modernizationera deceived by technological sophistication, including in the learning process in familyeducation. Wider coverage and very easy access by every human being, the internet has becomea very important thing in the process of family education in the Millennial Era